Combined metabolome and transcriptome analysis reveals the key pathways involved in the responses of soybean plants to high Se stress - Ying Liu; Jianyu Li; Jianning Shi; Yuhu Pan; Shaoxia Yang; Yingbin Xue (Ecotoxicology and Environmental Safety)
High selenium (Se) levels can induce toxicity, inhibit growth, and affect gene expression and metabolite content in plants. However, the molecular mechanism by which high Se stress affects soybean plants remains unclear. This study examined the responses of soybean leaves and roots to high Se stress using transcriptome and metabolome analyses. High Se stress significantly inhibited soybean root growth, reduced leaf area, and affected the antioxidant enzyme system in roots and leaves, resulting in the accumulation of malondialdehyde (MDA). High Se stress increased indoleacetic acid (IAA), abscisic acid (ABA), jasmonic acid (JA), and salicylic acid (SA) in the roots by 3.34-fold, 8.94-fold, 0.25-fold, and 5.65-fold, respectively. Similarly, high Se stress increased IAA, ABA, JA, and SA in the leaves by 1.96-fold, 10.54-fold, 2.03-fold, and 4.22-fold, respectively. In addition, high Se stress affected ion absorption and transport in soybean plants. Transcriptome results showed that there were 10,038 differentially expressed genes (DEGs) in soybean roots and 5811 DEGs in leaves, which affected the expression of antioxidant enzymes, ion transport and hormone-related genes. Metabolome results revealed that there were 277 differentially expressed metabolites (DEMs) in soybean leaves and 312 DEMs in roots. Soybean roots and leaves were significantly enriched in the ''β-alanine metabolism'' pathway under high Se stress, with differential expression of Aldehyde dehydrogenase (ALDH), Amine oxidase (AO), and other related genes, thereby relieving oxidative stress. This study improves our understanding of the molecular mechanisms underlying the responses of soybean plants to high Se stress and provides a basis for breeding Se-enriched soybean plants.